2021
DOI: 10.1186/s12877-021-02149-2
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and preparedness to provide care: interviews with individuals of different ages and with different caregiving experiences

Abstract: Background At present, the provision of informal care to older relatives is an essential pillar of the long-term care system in Germany. However, the impact of demographic and social changes on informal caregiving remains unclear. Methods Thirty-three semi-structured interviews were conducted with care consultants, informal caregivers and people without any caregiving experience to explore if people are willing to provide older adult care and how p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…For the availability of informal caregivers in a country, a key determinant is the willingness of individuals to provide the number of care hours required for the care-dependent person [ 4 ]. Even though the needed care time per day or the expected duration of caregiving is difficult to plan ahead [ 6 ], it is important to know what people can imagine in terms of providing informal care. Studies show that with increasing care dependency, the necessary care time per day is often higher than our maximum level of 8 h care time per day [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the availability of informal caregivers in a country, a key determinant is the willingness of individuals to provide the number of care hours required for the care-dependent person [ 4 ]. Even though the needed care time per day or the expected duration of caregiving is difficult to plan ahead [ 6 ], it is important to know what people can imagine in terms of providing informal care. Studies show that with increasing care dependency, the necessary care time per day is often higher than our maximum level of 8 h care time per day [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a systematic literature review of the scientific databases PubMed, Scopus, and Dimdi [ 26 ] and 33 semi-structured qualitative interviews [ 6 , 27 ] were used to identify the most relevant attributes and corresponding levels. While the type and severity of a care dependency as well as the (relationship to) the care-dependent person are important determinants for a person’s willingness to provide care [ 6 ], we decided to solely focus on relevant attributes that describe informal caregiving situations in the DCE. Five quantitative attributes with three levels each were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking responsibility for caring for a person requires the combination of two conditions: availability to provide care and adequacy to do so [ 33 ]. In fact, assuming the responsibility of caring for a person with dependencies may signify, for those who are not prepared, a largely negative impact on their well-being, characterized as a state of burden [ 32 , 33 ]. When the burden of care exceeds the capacity of the informal caregiver, then situations of anxiety (#7, #1), depression (#1), fear (#7), and stress (#1, #2, #6) may arise.…”
Section: Discussionmentioning
confidence: 99%
“…provide care. Many scholars directly built their work on the model (for instance, Brettschneider et al 2019 ; Calvó-Perxas et al 2018 ; de Jong et al 2021 ; Kaschowitz & Brandt 2017 ; Palmer 2019 ; Peng and Anstey 2019 ; Suanet et al 2019 ; Verbakel, et al 2017 ; Vos et al 2020 ). Directly empirical assessing the Informal Care Model , de Klerk et al ( 2021 ) identified, in line with the Informal Care Model , both sociodemographic factors as well as individual barriers and beliefs as determinants for different types of informal care relationships in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%